Khat and alcohol use and risky sex behaviour among in-school and out-of-school youth in Ethiopia - Kebede, Derege (BioMed Central, 2005)
BACKGROUND: Khat (an evergreen plant with amphetamine-like properties) and alcohol are widely consumed among the youth of Ethiopia. However, their relationship to risky sexual behaviour is not well described. This study was conducted to describe the magnitude of risky sexual behaviour (unprotected sex and early initiation of sexual activity) and its association with Khat and alcohol consumption in Ethiopian youths. METHODS: A probabilistic national sample of 20,434 in-school and out-of-school youths aged between 15 and 24 years of age was selected and interviewed regarding their sexual behavior and substance use. RESULTS: Over 20% of out-of-school youth had unprotected sex during the 12-month period prior to interview compared to 1.4% of in-school youth. Daily Khat intake was also associated with unprotected sex: adjusted OR (95% CI) = 2.26 (1.92, 2.67). There was a significant and linear association between alcohol intake and unprotected sex, with those using alcohol daily having a three fold increased odds compared to those not using it: adj. OR (95% CI) = 3.05 (2.38, 3.91). Use of substances other than Khat was not associated with unprotected sex, but was associated with initiation of sexual activity: adj. OR (95% CI) = 2.54 (1.84, 3.51). CONCLUSION: A substantial proportion of out-of-school youth engage in risky sex. The use of Khat and alcohol and other substances is significantly and independently associated with risky sexual behaviour among Ethiopian youths.